Third-line treatment with second-generation tyrosine kinase inhibitors (dasatinib or nilotinib) in patients with chronic myeloid leukemia after two prior TKIs: real-life data on a single center experience along with the review of the literature. Issue 4 (21st April 2018) - Ongoren, Seniz; Eskazan, Ahmet Emre; Suzan, Veysel; Savci, Sercan; Erdogan Ozunal, Isil; Berk, Selin; Yalniz, Fevzi Fırat; Elverdi, Tugrul; Salihoglu, Ayse; Erbilgin, Yucel; Iseri, Sibel Aylin; Ar, Muhlis Cem; et al.
ABSTRACT: Objectives: Newer tyrosine kinase inhibitors (TKIs) (bosutinib, ponatinib) and allogeneic hematopoietic stem cell transplantation (allo-HSCT) can be utilized as a salvage therapy in patients with chronic myeloid leukemia (CML) who failed two lines (imatinib → nilotinib or imatinib → dasatinib) of TKI therapy. However, these TKIs are not available in many countries and not all patients can undergo allo-HSCT. Methods: In this study, CML patients who received dasatinib or nilotinib as a third-line treatment were retrospectively evaluated. Results: Out of 209 patients, third-line dasatinib/nilotinib was administered in 21. During the follow-up, 16 out of 21 patients gained and/or maintained an optimal response, and 4 patients died due to progression. Seventeen patients were alive at the time of the analysis, of which 13 were still on TKI, whereas 4 patients quit treatment. Discussion: In patients failing two lines of TKI, dasatinib or nilotinib can be beneficial and safely administered as a third-line treatment especially in nations with restricted resources.